A rare variation of formation of median nerve - a case report - S Monica Diana; Ramesh Kumar Subramanian; S Senthil Kumar (Wolters Kluwer Medknow Publications, 2015)
Many variations have been reported regarding formation of the brachial plexus and its branches. Here the authors report a rare variation pertaining to lateral cord of median nerve. During routine dissection,at Sri Ramachandra Medical College and Hospital,Chennai, in the department of anatomy, in a male cadaver in the right upper limb, the authors found an additional lateral root from lateral cord joining the medial root to form the median nerve. Musculocutaneous nerve did not pierce the coracobrachialis muscle instead it gave a direct branch to the muscle. Nerve supply to biceps and brachialis were of normal pattern. The musculo cutaneous nerve communicated with the median nerve before supplying other muscles. Median nerve was medial throughout the arm but about 7cm above the level of medial epicondyle it crossed the brachial artery from medial to lateral.Morphometry of the nerves were studied by measurements. Knowledge of these variations and measurements will be helpful during surgical and anaesthetic procedures in the axilla.